Exploring transformative policy imaginaries for a sustainable Post-COVID society - Giurca Alexandru; Befort Nicolas; Taylor Amos (Elsevier, 2022)
The COVID-19 crisis and its underlying health, socio-economic and environmental challenges warrants a discussion about transformative policies for a more sustainable, post-pandemic world. At EU level, policy packages and initiatives such as the European Green Deal (EGD), the Bioeconomy Strategy (BES) or the Circular Economy Action Plan (CEAP) may have the prerequisites to support a sustainable socio-economic transformation. But can these initiatives live up to public imaginaries of a sustainable post-pandemic world? To answer this question, we conducted a qualitative media analysis in order to outline emerging public imaginaries, as well as different policy suggestions put forth by different media outlets. We then grouped these imaginaries into seven major themes ranging from finance to resource management and city planning. With the help of the Delphi approach, we discussed these themes with a panel of ten international experts in order to scope for different transformative policy options. The public imaginaries we identified represent a mix of imaginaries underpinned by different political ideologies, economic philosophies and sustainability rationales. The highest expectations were connected to the EGD, although none of the EU policy packages can singlehandedly tackle the urgent sustainability challenges posed by the pandemic. However, the current trajectory of the EGD is geared towards the business-as-usual. We discuss how EU policies can overcome this limitation and imagine more radical transformation pathways in order to jumpstart a sustainable post-COVID recovery that goes beyond pursuing green growth.